CYP2J2/EET reduces vulnerability to atrial fibrillation in chronic pressure overload mice - Li, Xuguang (J Cell Mol Med, 2019)
Growing evidence has well established the protective effects of CYP2J2/EET on the cardiovascular system. The aim of the present study was to determine whether CYP2J2/EET has a preventive effect on atrial fibrillation (AF) and to investigate the underlying mechanisms. Wild‐type mice were injected with or without AAV9‐CYP2J2 before abdominal aortic constriction (AAC) operation. After 8 weeks, compared with wild‐type mice, AAC mice display higher AF inducibility and longer AF durations, which were remarkably attenuated with AAV9‐CYP2J2. Also, AAV9‐CYP2J2 reduced atrial fibrosis area and the deposit of collagen‐I/III in AAC mice, accompanied by the blockade of TGF‐β/Smad‐2/3 signalling pathways, as well as the recovery in Smad‐7 expression. In vitro, isolated atrial fibroblasts were administrated with TGF‐β1, EET, EEZE, GW9662, SiRNA Smad‐7 and pre‐MiR‐21, and EET was demonstrated to restrain the differentiation of atrial fibroblasts largely dependent on Smad‐7, due to the inhibition of EET on MiR‐21. In addition, increased inflammatory cytokines, as well as activated NF‐κB pathways induced by AAC surgery, were also significantly blunted by AAV9‐CYP2J2 treatment. These effects of CYP2J2/EET were partially blocked by GW9662, the antagonist of PPAR‐γ. In conclusion, this study revealed that CYP2J2/EET ameliorates atrial fibrosis through modulating atrial fibroblasts activation by disinhibition of MiR‐21 on Smad‐7, and attenuates atrial inflammatory response by repressing NF‐κB pathways, reducing the vulnerability to AF, and CYP2J2/EET exerts its role at least partially through PPAR‐γ activation. Our findings might provide a novel upstream therapeutic strategy for AF.